The Effect of Ecological Factors on the Distribution of Myormoph Rodent Pest Species Infesting the University of Eldoret Farms, Uasin Gishu County, Kenya - Werunga, M.; Mwaniki , D. M.; Wanjala, F. M. E. (Africa Environmental Review Journal, 2022)
Rodents are recognized ecologically as one of the most important pests of cereals. Rodents occur in a wide range of terrestrial habitat, they are diverse and form an integral part of ecosystem functioning. Rodents are pests of concern in Kenya, as they cause considerable damage to cereal crops before and after harvest and therefore affect food security by impacting on both food availability and safety. However, knowledge of the factors that affect their population and distribution in Kenya is limited. The objective of the research was to determine the effect of ecological factors namely rainfall, relative humidity and temperature on the incidences and distribution of gender, type of species and population myomorph rodent pests infesting maize and wheat farms at University of Eldoret, Uasin Gishu County, Kenya. Grids of 70 m x 70 m crop cuttings was done in commercial fields of maize and wheat both locally woven live traps and Sherman’s live traps were used to capture rodents with peanut butter and sun dried Omena (Rastrineobola argentea) used as baits. The ecological factors of rainfall, relative humidity and temperature data were obtained from the metrological station based at Eldoret international airport. Three types of myomorph rodent pest species were captured and identified being Mastomys natalensis, Arvicanthis niloticus and Lemniscomys striatus. A Pearson correlation indicated a very weak positive correlation between rainfall and gender (males and females) distribution (r = 0.171, P = 0.001). A very weak linear positive correlation was observed between relative humidity and gender (r = 0.198, P = 0.001) that was statistically significant (P < 0.01). Rainfall and relative humidity had an effect on distribution of gender (males and females). However, there was a very weak positive correlation between temperature and gender in year one and two (r = 0.056, P=0.225; r =0.093 =0.214) and weak negative correlation in year three (r = -0.046, P=0.449) with no statistically significant difference of temperature on gender distribution (P > 0.001). Pearson correlations between ecological factors of rainfall, relative humidity and temperature showed a linear weak correlation with species distribution (r =-0.001, P= 0.986).The ecological factors rainfall, relative humidity were shown to influence species and gender distribution but temperature did not have any notable influence on species distribution during the present study.